Development of Competitive Strategies in the "Clarinet" (Clustering and Networking) Model in Private Schools to Increase Student Interest - Penta Karuni Hapsari; Listyani Listyani; Bambang Ismanto (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2024)
This research aims to describe the framework for developing competitive strategies for schools using “Clarinet” (clustering and networking) models, as well as to assess the feasibility of the development guide for competitive strategies in “Clarinet” models. This research uses a qualitative approach with the Research and Development (R&D) method by Borg and Gall. Data collection is conducted through questionnaires, documentation studies, in-depth interviews, and Focus Group Discussions (FGD). Data collection is done through documentation studies, interviews, questionnaires, and focus group discussions. The data analysis is conducted through the triangulation of techniques and sources. The results show that the validation test for the feasibility of the model and competitive strategies by education management experts yielded 88%, and marketing management experts yielded 96%. The research results indicate that the trial of the competitive strategy product using clustering and networking models is approximately 94% (very good/very valid). It is concluded that the competitive strategy within clustering and networking models is worthy of implementation to enhance the interest of students.